2009
DOI: 10.1097/bpo.0b013e3181b76933
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Classification of Chronic Hematogenous Osteomyelitis in Children

Abstract: The results suggest that our classification system for chronic hematogenous osteomyelitis in children is reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 14 publications
1
28
1
Order By: Relevance
“…This classification system also allows description of physeal damage to long bones. It has been shown to have good inter-and intra-observer reliability, 19 and in practice the authors have found that it is useful in planning surgical management.…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This classification system also allows description of physeal damage to long bones. It has been shown to have good inter-and intra-observer reliability, 19 and in practice the authors have found that it is useful in planning surgical management.…”
Section: Classificationmentioning
confidence: 99%
“…The Beit Cure classification system was developed specifically for chronic haematogenous osteomyelitis in children 19 ( Fig. 1).…”
Section: Classificationmentioning
confidence: 99%
“…In Gambia, for example, osteomyelitis accounted for 7.8% of paediatric surgical admissions and 15.4% of inpatient's days. [8] Due to the way of living, traditions and the social situation, osteomyelitis plays an important role in the developing countries. [8][9][10] In the industrialised countries, post-traumatic osteomyelitis plays only a minor role in children, in contrast to adults.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic osteomyelitis may present with a relatively small focus of disease surrounded by a strong reaction of the host bone, which walls off the infection. This is termed a Brodie abscess, and is characterized by a necrotic center, a well-defined inner border, and a hazy, ill-defined and broader halo of infection [37]. A less well-contained focus of osteomyelitis can develop a necrotic center or sequestrum, surrounded by pus.…”
Section: Imaging Of Complicationsmentioning
confidence: 99%